2011
DOI: 10.1093/cid/cir179
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency Triazole Resistance Found In Nonculturable Aspergillus fumigatus from Lungs of Patients with Chronic Fungal Disease

Abstract: The very low organism burdens of fungi causing infection have previously prevented direct culture and detection of antifungal resistance in clinical samples. These findings have major implications for the sustainability of triazoles for human antifungal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
245
6
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 273 publications
(255 citation statements)
references
References 43 publications
(53 reference statements)
3
245
6
1
Order By: Relevance
“…Thus, case detection is likely to be incomplete. Detectable Aspergillus desoxyribonucleic acid (DNA) in respiratory samples 36 could suggest CPA, prior to A. fumigatus IgG antibodies being requested.…”
Section: Cpa Case Ascertainmentmentioning
confidence: 99%
“…Thus, case detection is likely to be incomplete. Detectable Aspergillus desoxyribonucleic acid (DNA) in respiratory samples 36 could suggest CPA, prior to A. fumigatus IgG antibodies being requested.…”
Section: Cpa Case Ascertainmentmentioning
confidence: 99%
“…A. fumagatis is a ubiquitous fungal antigen and the most common fungus in the airway, inhaled at a rate of several hundred conidia per day. [76][77][78] Although studies in mice found that a single exposure to A. fumagatis induced increases in Treg numbers and function in the lung, repeated exposure models, more akin to the exposure humans experience, was found to shift T-cell responses toward a pathogenic Th2-Th17 phenotype. 79 The secosteroid hormone 1,25-dihydroxyvitamin D3 (1,25[OH]D 3 ) has been shown in multiple disease states to induce Tregs.…”
Section: Potential Causes Of Treg Dysfunctionmentioning
confidence: 99%
“…All the primers were selected based on pervious study [10]. Wild type strains A. fumigatus Cyp51A gene (GenBank accession number AF338659.1) and A. niger Cyp51A gene (GenBank accession number JF450900) were used as reference.…”
Section: Primers For Pcr Assays and Sequencingmentioning
confidence: 99%